PTU-231 Bowel preparation for inpatient colonoscopy: an audit of quality and outcomes. (28th May 2012) - Aldridge, M; Phillips, A; Gee, I
Abstract : Introduction: It is well recognised that inpatient colonoscopy is more problematic than outpatient colonoscopy, with poorer quality of bowel preparation 1 and reduced rates of successful completion of the procedure among inpatients. 2 We aimed to measure the quality of bowel preparation and the success rate of inpatient colonoscopy in a large district general hospital. Methods: All patients undergoing inpatient colonoscopy at Worcestershire Royal Hospital between 1 September 2010 and 1 September 2011 were identified retrospectively using paper-based documentation available in the Endoscopy department. The computerised colonoscopy reports (Unisoft, Enfield, UK) were then obtained for these patients. Standard bowel preparation for these patients was two sachets of Picolax, one the evening before and one the following morning, with colonoscopy performed on an afternoon list. Successful colonoscopy was defined as intubation of the caecum with "excellent" or "good" bowel preparation. Results: We identified 50 patients undergoing inpatient colonoscopy, with a median age of 74 (IQR 62–80), representing 3% of all colonoscopies done during this period. Approximately one-third (38%) were performed due to suspicious symptoms (most commonly PR bleeding), one-third (34%) were performed due to a CT abnormality, with the remainder predominantly due to unexplained anaemia (18%). Only 50% (25/50) of inpatient bowel preparation was rated by the endoscopist as "excellent" or "good, " compared with 86% overall for the same period (p<0.001 by χ 2 analysis). Among endoscopists with individual overall caecal intubation rates of >90%, the inpatient caecal intubation rate was only 74% (37/50). Out of the 13 failed inpatient intubations, 7 (54%) were due to poor bowel preparation. The remainder were due to patient discomfort (3), difficult angulation (2), and malignancy (1). In addition, the overall inpatient success rate was only 66% (33/50). In four cases (8%), although caecal intubation was achieved, poor bowel preparation meant a small lesion could not be excluded. Conclusion: This audit has demonstrated that the failure rate for inpatient colonoscopy is greater than outpatient procedures. The majority of these failures are due to poor bowel preparation. The reasons for this are complex, but may include reduced mobility and poorer adherence to bowel preparation and oral hydration. Deferring colonoscopy until after discharge from hospital is therefore advised whenever possible. Competing interests: None declared. References: 1. Ness RM, Manam R, Hoen H, et al. Predictors of inadequate bowel preparation for colonoscopy. Am J Gastroenterol 2001;96 :1797–802. 2. Hendry PO, Jenkins JT, Diament RH. The impact of poor bowel preparation on colonoscopy: a prospective single centre study of 10, 571 colonoscopies. Colorectal Dis 2007;9 :745–8.